The Role of Leaders’ Emotional Sincerity Towards Followers’ Trust: Leaders’ Integrity and Quality Relationship - Azeem, Qasim Ali Nisar, Muhammad; Hameed, Waseem ul; Waqas, Ali; Basheer, Muhammad Farhan; Hussain, Muhammad Sajjad (International Journal of Psychosocial Rehabilitation, 2020)
This study focused on the belief that followers assess the emotional sincerity of their leaders and consequently, it affects to followers’ perceived trust and their behaviors. It identified the key role of leaders’ emotional sincerity towards followers’’ outcomes (leaders integrity, quality relationship and trust in leaders). This study proposed a theoretical model on the basis of underpinning theory and empirical evidence. On the basis of literature support and underpinning theories, it is proposed that followers’ perceived emotional sincerity may a significant predictor and significantly influence to their leaders’ integrity and relationship quality. Moreover, leaders’ integrity and relationship quality (between leaders and followers) may affect followers’ trust in their leaders. Future studies may empirically test this model to gain insight understanding regarding the role of leaders’ emotional sincerity to shape the followers’ behaviors.